The Baltic Sea region after the Ukraine crisis and Trump: A Russian perspective - Alexander Sergunin (Danish Institute for International Studies (DIIS), 2019)
This DIIS Report identifies Russian national interests in the BSR (Baltic Sea Region) and discusses whether there are continuities and changes in these interests in the post-Crimea era. The Russian discourse on the BSR is explored, including Russian foreign policy schools and official foreign policy and national security doctrines. Different aspects of Moscow's BSR strategy - political, economic, sub-regional, environmental and military - are examined. The chances for Russia's participation in the BSR multilateral cooperative framework are assessed.
Keywords: 300; Internationale Beziehungen; Geopolitik; Ostseeraum; Russland